2005
DOI: 10.1189/jlb.0605317
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption in mice increases the proportion of peripheral memory T cells by homeostatic proliferation

Abstract: This study examined the mechanism underlying the increase of peripheral memory phenotype T cells that occurs during chronic alcohol consumption in mice. Female C57BL/6 mice were given 20% (w/v) alcohol in the drinking water for 2 weeks to 6 months. Chronic alcohol consumption significantly induced peripheral T cell lymphopenia; up-regulated expression of CD44 on T cells and increased the percentage of CD4+CD44int/hi and CD8+CD44int/hi Ly6C+ T cells; up-regulated the expression of CD43 on CD8+ T cells; increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 64 publications
(78 reference statements)
5
73
0
2
Order By: Relevance
“…Chronic ethanol consumption is linked to a number of abnormalities of the immune system, including lymphopenia, and downregulation of certain costimulatory molecules on the T cell surface (20), as well as to decreased interaction between leukocytes and endothelial cells (21). Chronic ethanol abuse will typically lead to severe medical consequences, but the potential of beneficial consequences of moderate alcohol intake have been discussed for decades, e.g., with respect to the epidemiology of cardiovascular diseases (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ethanol consumption is linked to a number of abnormalities of the immune system, including lymphopenia, and downregulation of certain costimulatory molecules on the T cell surface (20), as well as to decreased interaction between leukocytes and endothelial cells (21). Chronic ethanol abuse will typically lead to severe medical consequences, but the potential of beneficial consequences of moderate alcohol intake have been discussed for decades, e.g., with respect to the epidemiology of cardiovascular diseases (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that chronic alcohol consumption affects the immune system [20]. A large body of data indicates that chronic alcohol consumption in humans and mice activates the immune system, which is reflected in the activation of CD8 + T cells, dendritic cells (DC), and NKT cells, and increased production of pro-inflammatory cytokines such as IFN-γ and TNF-α [21-25]. We found that chronic alcohol consumption along with advancing growth of s.c. melanoma leads to inhibition in the expansion of memory and melanoma-specific CD8 + T cells, acceleration in the decay of Th1 cytokine producing CD8 + T cells [26], and compromised circulation of mature B cells [27].…”
Section: Introductionmentioning
confidence: 99%
“…We and others found that chronic alcohol consumption in the steady state increases the percentage of CD8 + T cells exhibiting the memory phenotype and also CD8 + T cells producing IFN-γ [ 31 , 33 ]. We further showed that chronic alcohol consumption increases memory T cells in the steady state through the induction of T cell homeostatic proliferation [ 33 ]. These increased memory and IFN-γ-producing CD8 + T cells in alcohol-consuming mice could play an important protective role in the antitumor immune response.…”
Section: Chronic Alcohol Consumption Inhibits B16bl6 Melanoma Lung Mementioning
confidence: 91%
“…The second is an antitumor function through presentation of antigen to T cells to enhance T cell activation and cytokine production. We found that in the steady state chronic alcohol consumption does not signifi cantly affect the B cell phenotype and nor their distribution in blood and lymph nodes; however, B cell numbers decrease in the spleen [ 33 ]. In melanoma-bearing mice B cells decrease around fourfold in the blood of alcoholconsuming mice with prolonged tumor growth compared to their water-drinking counterparts [ 70 ].…”
Section: Effects Of Chronic Alcohol Consumption On B Cellsmentioning
confidence: 95%